An early start at a professional soccer academy is no prerequisite for world cup soccer participation - Platvoet, Sebastiaan Willem-Jan; Heuveln, Germen van; Dijk, Jos van; Stevens, Tom; Niet, Mark de (Frontiers in Sports and Active Living, 2023)
Introduction: 829 players from 32 nations on five continents participated in the 2022 men's World Cup tournament in Qatar. Not much is known about the youth careers of World Cup players from all over the world, especially about the age at which they began playing professional youth soccer in a professional academy. This study aimed to provide insights in the age national team players participating in World Cup Qatar 2022 started playing for a professional youth soccer academy organization and whether their starting age relates to continent and their current playing position (i.e., goalkeepers, defenders, midfielders, and forwards).Method: Systematic online desk research was conducted to determine the age at which World Cup players started playing for professional youth soccer organizations. The median and interquartile ranges were expressed for the starting age in professional youth soccer organizations and the current age at the World Cup. The variables were compared with playing position, the continent of the player's World Cup nation, and the continent on which the player was raised.Results: The results reveal that World Cup Qatar 2022 players started playing for professional soccer youth academies soccer organizations at a median age of 13.2 years (range: 4.2 to 22.6). In Europe, players started playing for professional youth soccer organizations earlier than players on other continents (χ 2 (4) = 142.0, p<0.001). We also found a younger starting age in forwards than goalkeepers (p < 0.05).Discussion: In most established soccer nations, World Cup players started playing for professional soccer youthacademies soccer organizations before the age of 12. However, a significant number of players started later, especially players on other continents, which reveals the different pathways youth players can follow to the elites.